A composite additive and its application in lead-acid batteries

By using composite additives in lead-acid batteries, including staple fiber, graphite, antimony trioxide, stannous sulfate and TiB2@rGO composite guide materials, the structural deterioration problem of the positive electrode material during the circulation process is solved, the utilization rate and cycle life of the active substance are improved, and the rapid charging capacity of the battery is improved.

CN120221661BActive Publication Date: 2025-07-25SHANDONG JINKELI POWER SOURCES TECH +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510689903.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-05-27
Publication Date
2025-07-25
Estimated Expiration
2045-05-27

AI Technical Summary

Technical Problem

The existing lead-acid battery positive electrode materials are prone to structural deterioration during the circulation process, resulting in breakage of the electron transmission path, low utilization rate of active substances, rapid attenuation of capacity, and traditional conductive additives are difficult to meet the multiple requirements of conductive network stability, mechanical enhancement and interface protection at the same time.

Method used

Compound additives, including staple fiber, graphite, antimony trioxide, stannous sulfate, 4BS and TiB2@rGO composite conductors, are used to improve the overall electrical properties of the material through unique hydrophilic and conductive properties, forming a "hard and soft" structure, enhancing the utilization rate and circulation stability of active substances.

Benefits of technology

It significantly improves the utilization rate and cycle life of active substances of lead-acid batteries, improves the fast charging capacity and battery service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 6VCRJ4APMOEIQBCGDPJJET7LPHNY3N2IZR4WHA2Z
    Figure 6VCRJ4APMOEIQBCGDPJJET7LPHNY3N2IZR4WHA2Z
Patent Text Reader

Abstract

The present invention belongs to the technical field of lead-acid batteries, and specifically relates to a composite additive and its application in lead-acid batteries. The composite additive of the present invention comprises 0.3 to 2 parts of short fibers, 0.05 to 4 parts of graphite, 0.01 to 3 parts of antimony trioxide, 0.01 to 3 parts of stannous sulfate, 0.02 to 5 parts of 4BS, and 0.02 to 5 parts of TiB2@rGO composite conductive material. The composite additive provided by the present invention is environmentally friendly. When it is applied to the paste-making process to further prepare lead-acid batteries, it can improve the battery utilization rate and the service life of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lead-acid batteries, and particularly relates to a composite additive and its application in lead-acid batteries. Background Art

[0002] As one of the most mature technologies in the field of electrochemical energy storage, lead-acid batteries have long dominated in fields such as automotive starting power supplies, energy storage base stations, and backup power supplies due to their core advantages of low cost, high safety, and a perfect recycling system. However, with the continuous improvement of the requirements for the energy density, cycle life, and reliability of energy storage systems in the new energy industry, the performance bottleneck of the positive electrode materials of lead-acid batteries has become increasingly prominent, restricting their application in high-power and long-life scenarios. Since the positive electrode active material (PbO2) is prone to structural deterioration during the cycling process. The reasons for this are as follows. First, traditional conductive additives (such as carbon black and short fibers) are prone to migration or agglomeration during charge and discharge, resulting in the breakage of the electron transport path and the utilization rate of the active material being less than 50%. Second, the PbO2 particles soften and fall off due to volume expansion and insufficient mechanical strength, resulting in rapid capacity decay (the capacity retention rate is usually less than 70% after 500 cycles). Finally, an oxidation reaction occurs at the interface between the positive electrode grid (Pb-Ca-Sn alloy) and the active material at high potential, generating a high-impedance corrosion layer, further increasing the internal resistance and shortening the life.

[0003] In recent years, researchers have tried to improve the positive electrode conductivity by introducing nano-carbon materials (such as carbon nanotubes and graphene) or conductive polymers (such as polypyrrole and polyaniline). However, single-component additives are difficult to simultaneously meet the multiple requirements of conductive network stability, mechanical enhancement, and interface protection. For example, nano-carbon materials are prone to irreversible agglomeration due to van der Waals forces, resulting in deteriorated dispersibility; conductive polymers are limited by problems such as poor thermal stability and insufficient compatibility with lead-based materials.

[0004] CN105789711A discloses a high-performance lead-acid battery and its processing and assembly process. The positive electrode lead paste includes: antimony trioxide, stannous sulfate, graphite, polyester short fibers, pure water, sulfuric acid, lead powder, and tribasic lead sulfate; the negative electrode lead paste includes: graphite, lignin, barium sulfate, polyester short fibers, humic acid, pure water, sulfuric acid, lead powder, and tribasic lead sulfate. This makes the active substances in the lead paste have high strength and low formation difficulty. After assembling into a battery, the battery has a large initial capacity and a long cycle life. However, only graphite is used as the positive electrode additive for the conductive agent, which is easily corroded when subjected to electrochemical oxidation, resulting in the breakage of the electron transport path and low utilization rate of the active material. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a composite additive that is environmentally friendly, applied to lead-acid batteries, improves battery utilization, and extends the service life of the battery.

[0006] The composite additive described in the present invention, by weight, includes 0.3 parts to 2 parts of short fibers, 0.05 parts to 4 parts of graphite, 0.01 parts to 3 parts of antimony trioxide, 0.01 parts to 3 parts of stannous sulfate, 0.02 parts to 5 parts of 4BS (tetrabasic lead sulfate), and 0.02 parts to 5 parts of TiB2@rGO composite conductive material. (The above weight parts are all calculated based on 100 parts of lead powder).

[0007] The short fibers are organic synthetic fibers such as polyester, polypropylene, and acrylic fibers or carbon fibers, with a fineness of 0.2D to 5D and a length of 1.5 mm to 6 mm.

[0008] The preparation steps of the TiB2@rGO composite conductive material are as follows:

[0009] (1) Take titanium diboride ceramic powder, completely immerse it in concentrated nitric acid, perform pickling, then calcine it, and ultrasonically clean it to obtain a titanium diboride ceramic suspension;

[0010] (2) Mix the graphene oxide aqueous solution with the above-mentioned titanium diboride ceramic suspension, add a dispersant, and stir evenly to obtain a mixed solution coated with GO;

[0011] (3) Add a reducing agent to the mixed solution coated with GO to carry out a reduction reaction. After completion, wash it to obtain a TiB2@rGO composite;

[0012] (4) Completely immerse the TiB2@rGO composite in a silane coupling agent solution. After the reaction is completed, centrifuge the reaction solution, wash the obtained precipitate, and dry it to obtain the TiB2@rGO composite conductive material.

[0013] The particle size of the titanium diboride ceramic in step (1) is 3 μm to 10 μm, and the iron content is less than 500 ppm.

[0014] The pickling temperature in step (1) is 60 °C to 80 °C, and the pickling time is 2 h to 4 h; the calcination temperature in step (1) is 700 °C to 800 °C, and the calcination time is 1 h to 2 h. An oxide layer is formed on the surface of the titanium diboride ceramic after calcination. The mass concentration of concentrated nitric acid is 65%, and the calcination is carried out in an air atmosphere.

[0015] The mass ratio of graphene oxide to titanium diboride ceramic powder in step (2) is 1:5 to 1:10, and the concentration of the graphene oxide aqueous solution is 1 mg / mL to 5 mg / mL.

[0016] The dispersant in step (2) is polyethylene glycol with an average molecular weight of 4000, and the addition amount is 0.5% - 1% of the total mass of graphene oxide and titanium diboride ceramic powder.

[0017] The temperature for uniform stirring in step (2) is 60 - 80 °C, and the stirring time is 6h - 12h.

[0018] The reducing agent in step (3) is one of hydrazine hydrate, sodium borohydride, hydrogen sulfide, and hydroquinone, and the addition amount is 3% - 10% of the mass of graphene oxide. The reduction reaction temperature in step (3) is 90 °C - 120 °C, and the reduction time is 6h - 18h.

[0019] The silane coupling agent solution in step (4) is an ethanol solution of silane coupling agent with a mass concentration of 2% - 11%. The silane coupling agent is KH - 550. The pH of the silane coupling agent solution is first adjusted to 4.5 - 6 with acetic acid. The reaction temperature in step (4) is 60 °C - 80 °C, and the reaction time is 3h - 12h.

[0020] The specific operation for treating the reaction solution in step (4) is as follows: Transfer the reaction solution to a centrifuge tube, set the rotation speed to 4000 r / min and the centrifugation time to 10 min to precipitate the composite conductive material at the bottom of the centrifuge tube. Then slowly pour out the supernatant. Transfer the centrifugally precipitated composite conductive material to a beaker, add an appropriate amount of deionized water for washing. Stir evenly to fully dissolve the residual impurities, and then perform centrifugal separation again. This washing process is repeated 2 - 3 times to ensure complete removal of impurities. Spread the washed composite conductive material on a watch glass and place it in an oven, set the temperature to 80 °C, and the drying time to 24h.

[0021] The application of the composite additive includes the following steps: Apply it to the paste - making process to further prepare lead - acid batteries. The specific operation is as follows: Place the lead powder in a mixing device, turn on the stirring device, control the stirring speed at 100 r / min - 200 r / min, and then add each raw material of the composite additive, namely short fibers, graphite, antimony trioxide, stannous sulfate, and 4BS. After adding each raw material, continue to stir for 10 min - 15 min to mix evenly. Finally, add the TiB2@rGO composite conductive material, increase the stirring speed to 300 r / min - 400 r / min, and continue to stir for 30 min - 60 min to mix evenly for use in lead - acid batteries.

[0022] Specifically, the preparation steps of the TiB2@rGO composite conductive material are as follows:

[0023] (1) Take 3 μm~10 μm titanium diboride ceramic powder, immerse it in 65% concentrated nitric acid, and pickle it at 60℃~80℃ constant temperature with stirring for 2h~4h to remove impurities and generate hydroxyl groups, then calcine it at 700℃~800℃ in air atmosphere for 1h~2h to form an oxide layer on the surface, then add deionized water and ultrasonicate it for 30min to obtain a uniform suspension, i.e., titanium diboride ceramic suspension;

[0024] (2) According to the mass ratio of graphene oxide to titanium diboride ceramic powder of 1:5-1:10, 1 mg / mL-5 mg / mL of graphene oxide (GO) aqueous solution is mixed with the above-mentioned titanium diboride ceramic suspension, and 0.5%-1% of polyethylene glycol (PEG-4000) dispersant is added based on the mass of graphene oxide and titanium diboride ceramic powder. The mixture is stirred magnetically at 60°C-80°C for 6h-12h to allow GO to be adsorbed on the silicon carbide surface through hydrogen bonding and electrostatic effects to obtain a GO-coated mixed solution;

[0025] (3) Add 3% to 10% of the mass of graphene oxide as reducing agent to the mixed solution after GO coating, react at 90℃ to 120℃ for 6h to 18h to reduce GO to rGO, and finally, centrifuge and wash with deionized water for 3 times (speed 8000r / min, 10min each time) to remove residual hydrazine hydrate and obtain TiB2@rGO composite;

[0026] (4) Prepare a 2%~11% ethanol solution of silane coupling agent KH-550, adjust the pH to 4.5~6 with acetic acid to promote silane hydrolysis and bonding, and then completely immerse the TiB2@rGO composite in it, react at 60℃~80℃ for 3h~12h, so that the amino group and the hydroxyl group on the surface of titanium diboride are covalently bonded; the obtained reaction solution is transferred to a centrifuge tube, and the speed is set to 4000r / min and the centrifugation time is 10min, so that the composite conductor is precipitated at the bottom of the centrifuge tube, and then the supernatant is slowly poured out, and the composite conductor after centrifugation precipitation is transferred to a beaker, and an appropriate amount of deionized water is added for washing, and stirred evenly to fully dissolve the residual impurities, and centrifuged again. This washing process is repeated 2~3 times to ensure that the impurities are completely removed, and the washed composite conductor is spread on a watch glass, placed in an oven, and the temperature is set to 80℃ and the drying time is 24h to obtain a TiB2@rGO composite conductor. The TiB2@rGO composite conductor can effectively improve the overall electrical properties and dispersion stability of the material due to its unique hydrophilic and conductive properties, and significantly enhance the battery life, charge acceptance and active material utilization.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] (1)The composite additive of the present invention adds the TiB2@rGO composite conductive material. The conductive characteristics of large particle size titanium diboride ceramics and rGO form a conductive system. The strong composite between the amino-functionalized surface-enhanced titanium diboride formed by the silane coupling agent KH-550 and rGO is achieved. The high hydrophilicity of rGO makes the composite conductive material easily adsorb the electrolyte in the positive electrode plate of the battery, improving the utilization rate of the active material.

[0029] (2)When the composite additive of the present invention is applied to lead-acid batteries, the "rigid-flexible combination" structure is formed by the titanium diboride ceramic core and the rGO flexible layer, reducing the volume expansion stress, inhibiting the shedding of the active material, maintaining a high porosity retention rate of the electrode after cycling, and increasing the number of cycles.

[0030] (3)When the composite additive of the present invention is applied to batteries, the Grotthuss proton transport chain formed by the rGO conductive network and surface hydroxyl groups acts synergistically. Through the Maxwell-Wagner interfacial polarization effect, the formation of the electric double layer is accelerated, shortening the response time. The surface oxide layer and rGO form a dielectric gradient, improving the fast charging ability. Detailed implementation mode

[0031] The present invention will be further described below in conjunction with embodiments.

[0032] In Examples 1-3 below, the commercially available titanium diboride ceramic powder used has an iron content of less than 500 ppm and a particle size of 3 μm to 10 μm.

[0033] In Examples 4-6 and Comparative Example 1 below, the commercially available polyester staple fiber, polypropylene staple fiber, and carbon fiber used all have parameters meeting fineness of 0.2 D to 5 D and length of 1.5 mm to 6 mm.

[0034] The parameters of the commercially available graphite in Examples 4-6 and Comparative Example 1 are: natural flake graphite (D50 is 5 μm to 20 μm).

[0035] Example 1

[0036] The preparation steps of the described TiB2@rGO composite conductive material are as follows:

[0037] (1)Take titanium diboride powder with a particle size of 3 μm to 10 μm, immerse it in 65% concentrated nitric acid, stir at a constant temperature of 60 °C for 2 h for pickling, then calcine it at 700 °C for 2 h in an air atmosphere to form an oxide layer on the surface. Then add deionized water and ultrasonicate for 30 min to obtain a uniform suspension, that is, the titanium diboride ceramic suspension;

[0038] (2)According to a mass ratio of 1:5, mix the 1 mg / mL graphene oxide aqueous solution with the above-mentioned titanium diboride ceramic suspension, add 0.5% polyethylene glycol (PEG-4000) dispersant, and stir magnetically at 60 °C for 12 h to obtain a mixed solution coated with GO;

[0039] (3) Add 3% hydrogen sulfide to the GO-coated mixture and react at 90 °C for 18 h to reduce GO to rGO. Finally, centrifuge and wash with deionized water three times (rotation speed 8000 r / min, 10 min each time) to obtain the TiB2@rGO composite;

[0040] (4) Prepare an ethanol solution of 2% silane coupling agent KH-550, adjust the pH to 4.5 with acetic acid, then completely immerse the TiB2@rGO composite in it, react at 60 °C for 9 h, transfer the resulting reaction solution to a centrifuge tube, set the rotation speed to 4000 r / min and the centrifugation time to 10 min to precipitate the composite conductive material at the bottom of the centrifuge tube, then slowly pour off the supernatant, transfer the centrifuged and precipitated composite conductive material to a beaker, add an appropriate amount of deionized water for washing, stir evenly to fully dissolve the residual impurities, and perform centrifugal separation again. This washing process is repeated twice. Spread the washed composite conductive material flat on a watch glass and place it in an oven. Set the temperature to 80 °C and the drying time to 24 h to obtain the TiB2@rGO composite conductive material.

[0041] Example 2

[0042] The preparation steps of the described TiB2@rGO composite conductive material are as follows:

[0043] (1) Take titanium diboride ceramic powder with a particle size of 3 μm to 10 μm, immerse it in 65% concentrated nitric acid, stir at a constant temperature of 70 °C for 3 h for pickling, then calcine in an air atmosphere at 750 °C for 1.5 h to form an oxide layer on the surface, and then add deionized water and ultrasonicate for 30 min to obtain a uniform suspension, that is, a titanium diboride ceramic suspension;

[0044] (2) Mix the 2.5 mg / mL graphene oxide aqueous solution and the above-mentioned titanium diboride ceramic suspension according to a mass ratio of 1:7, add 0.6% polyethylene glycol (PEG-4000) dispersant, and stir magnetically at 70 °C for 8 h to obtain a GO-coated mixture;

[0045] (3) Add 7% sodium borohydride as a reducing agent to the GO-coated mixture and react at 100 °C for 12 h to reduce GO to rGO. Finally, centrifuge and wash with deionized water three times (rotation speed 8000 r / min, 10 min each time) to obtain the TiB2@rGO composite;

[0046] (4) Prepare an ethanol solution of 8% silane coupling agent KH-550, adjust the pH to 5 with acetic acid, then completely immerse the TiB2@rGO composite into it, react at 70 °C for 6 h, transfer the obtained reaction solution to a centrifuge tube, set the rotation speed at 4000 r / min and the centrifugation time at 10 min to precipitate the composite conductive material at the bottom of the centrifuge tube, then slowly pour out the supernatant, transfer the centrifuged and precipitated composite conductive material to a beaker, add an appropriate amount of deionized water for washing, stir evenly to fully dissolve the residual impurities, perform centrifugal separation again, repeat this washing process 3 times to ensure complete removal of impurities, spread the washed composite conductive material flat on a watch glass, put it into an oven, set the temperature at 80 °C and the drying time at 24 h to obtain the TiB2@rGO composite conductive material.

[0047] Example 3

[0048] The preparation steps of the described TiB2@rGO composite conductive material are as follows:

[0049] (1) Take titanium diboride ceramic powder with a particle size of 3 μm to 10 μm, immerse it in 65% concentrated nitric acid, stir at a constant temperature of 80 °C for 2 h for pickling, then calcine it in an air atmosphere at 800 °C for 2 h to form an oxide layer on the surface, and then add deionized water and ultrasonicate for 30 min to prepare a uniform suspension, that is, a titanium diboride ceramic suspension;

[0050] (2) Mix the 5 mg / mL graphene oxide aqueous solution and the above-mentioned titanium diboride ceramic suspension according to a mass ratio of 1:10, add 1% polyethylene glycol (PEG-4000) dispersant, and stir magnetically at 80 °C for 6 h to obtain a mixed solution coated with GO;

[0051] (3) Add 10% hydrazine hydrate as a reducing agent to the mixed solution coated with GO, react at 120 °C for 6 h to reduce GO to rGO, and finally, wash it 3 times by centrifugation with deionized water (rotation speed 8000 r / min, 10 min each time) to obtain the TiB2@rGO composite;

[0052] (4) Prepare an ethanol solution of 11% silane coupling agent KH-550, adjust the pH to 6 with acetic acid, then completely immerse the TiB2@rGO composite into it, react at 80 °C for 3 h, transfer the obtained reaction solution to a centrifuge tube, set the rotation speed at 4000 r / min and the centrifugation time at 10 min to precipitate the composite conductive material at the bottom of the centrifuge tube, then slowly pour out the supernatant, transfer the centrifuged and precipitated composite conductive material to a beaker, add an appropriate amount of deionized water for washing, stir evenly to fully dissolve the residual impurities, perform centrifugal separation again, repeat this washing process 3 times to ensure complete removal of impurities, spread the washed composite conductive material flat on a watch glass, put it into an oven, set the temperature at 80 °C and the drying time at 24 h to obtain the TiB2@rGO composite conductive material.

[0053] Example 4

[0054] The TiB2@rGO composite conductive material of this embodiment utilizes the TiB2@rGO composite conductive material prepared in Example 1, and the short fibers are polyester staple fibers.

[0055] The composite additive includes, by weight, 0.3 parts of short fibers, 0.05 parts of graphite, 0.01 parts of antimony trioxide, 0.01 parts of stannous sulfate, 5 parts of 4BS, and 5 parts of TiB2@rGO composite conductive material. (Based on 100 parts by weight of lead powder).

[0056] Example 5

[0057] The TiB2@rGO composite conductive material of this embodiment utilizes the TiB2@rGO composite conductive material prepared in Example 2, and the short fibers are carbon fibers.

[0058] The composite additive includes, by weight, 2 parts of short fibers, 4 parts of graphite, 3 parts of antimony trioxide, 3 parts of stannous sulfate, 3 parts of 4BS, and 3 parts of TiB2@rGO composite conductive material. (Based on 100 parts by weight of lead powder).

[0059] Example 6

[0060] The TiB2@rGO composite conductive material of this embodiment utilizes the TiB2@rGO composite conductive material prepared in Example 3, and the short fibers are polypropylene staple fibers.

[0061] The composite additive includes, by weight, 1 part of short fibers, 1 part of graphite, 0.5 parts of antimony trioxide, 0.5 parts of stannous sulfate, 0.02 parts of 4BS, and 0.02 parts of TiB2@rGO composite conductive material. (Based on 100 parts by weight of lead powder).

[0062] Comparative Example 1

[0063] The short fibers in this comparative example are polyester staple fibers.

[0064] The composite additive includes, by weight, 2 parts of short fibers, 4 parts of graphite, 2 parts of antimony trioxide, 3 parts of stannous sulfate, 3 parts of 4BS. (Based on 100 parts by weight of lead powder).

[0065] Comparative Example 2

[0066] The preparation steps of a TiB2@rGO composite conductive material not modified by silane coupling agent K-550 are as follows:

[0067] (1) Take titanium diboride ceramic powder with a particle size of 3 μm to 10 μm, immerse it in 65% concentrated nitric acid, stir at a constant temperature of 60 °C for 2 h for pickling, then calcine it at 700 °C in an air atmosphere for 2 h to form an oxide layer on the surface. Then add deionized water and ultrasonicate for 30 min to obtain a uniform suspension, namely titanium diboride ceramic suspension;

[0068] (2) Mix the aqueous solution of graphene oxide with a concentration of 1 mg / mL and the above-mentioned titanium diboride ceramic suspension according to a mass ratio of 1:5, add 0.5% polyethylene glycol (PEG - 4000) dispersant, and stir magnetically at 60 °C for 12 h to obtain a mixed solution coated with GO;

[0069] (3) Add 3% reducing agent hydrogen sulfide to the mixed solution coated with GO, react at 90 °C for 18 h to reduce GO to rGO. Finally, centrifuge and wash with deionized water 3 times (rotation speed 8000 r / min, 10 min each time), spread the washed TiB2@rGO composite conductive material on a petri dish, put it into an oven, set the temperature to 80 °C, and the drying time to 24 h to obtain the TiB2@rGO composite conductive material without modification by silane coupling agent K - 550.

[0070] In the following composite additives, the TiB2@rGO composite conductive material is the TiB2@rGO composite conductive material without modification by silane coupling agent K - 550. The short fiber is polyester staple fiber.

[0071] A composite additive, by weight, includes 1 part of short fiber, 1 part of graphite, 0.5 part of antimony trioxide, 0.5 part of stannous sulfate, 0.02 part of 4BS, and 0.02 part of TiB2@rGO composite conductive material. (Based on 100 parts by weight of lead powder).

[0072] Application:

[0073] (1) The composite additives in Examples 4 - 6 and Comparative Examples 1 - 2 above are prepared into positive lead paste according to the following steps to obtain lead - acid batteries: (The added weight parts of each substance are all added based on 100 weight parts of the total lead powder);

[0074] (2) Power on the equipment and start it. Pour half of the weight part of the formulated amount of lead powder into the paste mixer, then add the composite additives in the formulated amounts of Examples 4 - 6 and Comparative Examples 1 - 2, and then pour the other half of the weight part of the lead powder into the paste mixer. Cover the lid and run the program. After two minutes, slowly pour 11 parts of pure water into the paste mixer, and slowly add 8 parts of dilute sulfuric acid with a density of 1.4 g / cm 3 into the paste mixer; When measuring that the temperature of the lead paste < 45 °C and the apparent density is between 4.44 and 4.55 g / mL, the positive lead paste is prepared;

[0075] (3)Plate coating and curing: Place the grid on a glass plate, and use a coating knife to evenly apply the lead paste onto the grid. After acid drenching, pressing, curing and drying, and plate separation, the green plates are obtained.

[0076] (4)Battery assembly: Group the positive and negative plates in an alternating arrangement, insert an AGM separator in the middle, weld the bus bar, then place it into the battery case and seal the cover with epoxy resin. The negative plates use the same batch.

[0077] (5)Acid injection and formation: After acid injection and liquid injection, let it stand for 4 h to ensure that the plates are fully wetted. After charge-discharge cycling, remove the acid and install the safety valve to obtain a single cell battery.

[0078] Test the performance indicators of the batteries prepared above according to GB / T22199.1-2017. The experimental results are shown in Table 1:

[0079] 1) 2hr improvement rate

[0080] Experimental parameters: 2hr capacity, time, temperature.

[0081] 2) Cycle life

[0082] Important experimental parameters: number of cycles, discharge voltage, temperature.

[0083] 3) Fast charging ability (the proportion of increased discharge capacity)

[0084] Important experimental parameters: discharge capacity, discharge time, temperature.

[0085] Specifically, the proportion of increased discharge capacity is ; Cb1: Discharge capacity during normal charging; Cb2: Discharge capacity during fast charging.

[0086] When discharging for 1.60 h and the battery terminal voltage is continuously lower than 1.75 V three times, it is considered that the battery cycle life ends, and these three cycles are not included in the number of cycles.

[0087] Table 1 Test results

[0088]

[0089] The improvements in both the 2hr improvement rate and the fast charging ability are based on the comparison with Comparative Example 1. From the test results in Table 1 above, it can be seen that through the hydrophilic modification of titanium diboride and the composite coating of graphene, combined with the synergistic effect of multiple components, the present invention significantly improves the battery life, charging ability and active material utilization rate.

Claims

1. A composite additive, characterized in that, By weight parts, it includes 0.3 parts to 2 parts of short fibers, 0.05 parts to 4 parts of graphite, 0.01 parts to 3 parts of antimony trioxide, 0.01 parts to 3 parts of stannous sulfate, 0.02 parts to 5 parts of 4BS, and 0.02 parts to 5 parts of TiB2@rGO composite conductive material.

2. The composite additive according to claim 1, characterized in that, The short fibers have a fineness of 0.2D to 5D and a length of 1.5 mm to 6 mm.

3. The composite additive according to claim 1, wherein The preparation steps of the TiB2@rGO composite conductive material are as follows: (1) Take TiB2 powder, completely immerse it in concentrated nitric acid, perform pickling, then calcine it, and ultrasonically clean it to obtain a TiB2 suspension; (2) Mix the graphene oxide aqueous solution with the above TiB2 suspension, add a dispersant, and stir evenly to obtain a mixed solution coated with GO; (3) Add a reducing agent to the mixed solution coated with GO to carry out a reduction reaction, and after completion, wash it to obtain a TiB2@reduced graphene oxide composite; (4) Completely immerse the TiB2@reduced graphene oxide composite in a silane coupling agent solution. After the reaction is completed, centrifuge the reaction solution, wash the obtained precipitate, and dry it to obtain the TiB2@rGO composite conductive material.

4. The composite additive according to claim 3, characterized in that The particle size of the TiB2 is 3 μm to 10 μm, and the iron content is less than 500 ppm.

5. The composite additive according to claim 3, characterized in that, In step (1), the pickling temperature is 60°C to 80°C, and the pickling time is 2 h to 4 h; in step (1), the calcination temperature is 700°C to 800°C, and the calcination time is 1 h to 2 h.

6. The composite additive according to claim 3, characterized in that In step (2), the mass ratio of graphene oxide to TiB2 powder is 1:5 to 1:10; the concentration of the graphene oxide aqueous solution is 1 mg / mL to 5 mg / mL.

7. The composite additive according to claim 3, wherein In step (2), the dispersant is polyethylene glycol with an average molecular weight of 4000, and the addition amount is 0.5% to 1% of the sum of the masses of graphene oxide and TiB2 powder; the temperature for stirring evenly in step (2) is 60°C to 80°C, and the stirring time is 6 h to 12 h.

8. The composite additive according to claim 3, wherein In step (3), the reducing agent is one of hydrazine hydrate, sodium borohydride, hydrogen sulfide, and hydroquinone, and the addition amount is 3% to 10% of the mass of graphene oxide; the reduction reaction temperature in step (3) is 90°C to 120°C, and the reduction time is 6 h to 18 h.

9. The composite additive according to claim 3, characterized in that, In step (4), the silane coupling agent solution is an ethanol solution of a silane coupling agent with a mass concentration of 2% to 11%, and the silane coupling agent is KH-550; the silane coupling agent solution is first adjusted to a pH of 4.5 to 6 with acetic acid; the reaction temperature in step (4) is 60°C to 80°C, and the reaction time is 3 h to 12 h.

10. Use of the composite additive according to any one of claims 1-9 in a lead-acid battery, characterized in that, Apply the composite additive to the paste-making process to further prepare a lead-acid battery.

Citation Information

Patent Citations

  • High-performance lead-acid storage battery and machining-assembling process thereof

    CN105789711A

  • Graphene coated lead powder composite material and application thereof

    CN103579616A

  • Secondary cell with high recharging efficiency and long term stability

    US20170301960A1